PENGARUH WAKTU DAN JENIS INDUSTRI PADA STRATEGI MANAJEMEN MODAL KERJA: SURVEY PADA INDUSTRI OTOMOTIF, GARMENT DAN MAKANAN DI BURSA EFEK JAKARTA - Pramono, Joko; Khatimah, Husnul (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
Working capital inventories is strategic activity, total of working capital influence by choice of strategic organization. Research founding indicates that working capital ratio depend on industry but not on time and interaction of industries and time. This is suggested that firm must optimized the total working capital